Effects of school closures on displaced students and future cohorts in Sweden 2000-2016 - Jonas Larsson Taghizadeh (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
The aim of this paper is to investigate the effects of school closures on student achievement among displaced students and future cohorts in Sweden. In contrast to previous studies that only analyze the effects of school closures on displaced students, this study also takes account of the effects on subsequent cohorts of students who never experience the disruption of the move. Furthermore, the study is one of the first quantitative studies to estimate the effects of school closures outside the US. The effects are analyzed using a quasi-experimental study on all public middle school closures in Sweden 2000-2012, a majority of them located in cities. The study utilizes a design that provides a better control for family background compared to previous studies on school closures and that makes it possible to study the effects on future cohorts. The performance of students who graduated from closed Swedish middle schools are compared with the performance of their "treated" younger siblings who were expected to graduate from the same schools but as a result of the closures attended other schools. The results suggest that the school closures in Sweden overall had no effects on student achievement, even though displaced students and future cohorts attended slightly higher-performing schools than their siblings as a result of the closures. Contrary to theoretical expectations, the effects on displaced students are very similar to the effects on future cohorts, suggesting that the disruption effects were close to zero. Furthermore, the extensive school voucher system in Sweden does not seem to direct students to higher quality schools after school closures.
Keywords: H44; I21; I28; 330; School closures; school choice; student achievement; disruption effects